Late Talkers: A Population-Based Study of Risk Factors and School Readiness Consequences - Hammer, Carol Scheffner (J Speech Lang Hear Res, 2017)
PURPOSE: This study was designed to (a) identify sociodemographic, pregnancy and birth, family health, and parenting and child care risk factors for being a late talker at 24 months of age; (b) determine whether late talkers continue to have low vocabulary at 48 months; and (c) investigate whether being a late talker plays a unique role in children's school readiness at 60 months. METHOD: We analyzed data from the Early Childhood Longitudinal Study, a population-based sample of 9,600 children. Data were gathered when the children were 9, 24, 48, and 60 months old. RESULTS: The risk of being a late talker at 24 months was significantly associated with being a boy, lower socioeconomic status, being a nonsingleton, older maternal age at birth, moderately low birth weight, lower quality parenting, receipt of day care for less than 10 hr/week, and attention problems. Being a late talker increased children's risk of having low vocabulary at 48 months and low school readiness at 60 months. Family socioeconomic status had the largest and most profound effect on children's school readiness. CONCLUSIONS: Limited vocabulary knowledge at 24 and 48 months is uniquely predictive of later school readiness. Young children with low vocabularies require additional supports prior to school entry.